Reconstruction Of Regional Autonomy To Strengthen Governor's Authority - Bambang Sugianto; Febrian Febrian; Ridwan Ridwan; Iza Rumesten (Faculty of Law, Universitas Pekalongan, 2023)
Autonomy is one of the essences of realizing regional independence and accelerating development, so that the community will enjoy development through the role of local governments that involve the community directly in development based on local wisdom. However, in the implementation of regional autonomy, problems arise and there are still many regions that are not prosperous and unable to make it happen. To get out of the problems faced in the implementation of autonomy, reconstruction of several inhibiting factors is carried out, namely: exploitation of regional income, understanding of the concept of decentralization and regional autonomy that is not yet stable, provision of inadequate regulations for implementing regional autonomy , human resources of government officials who have not fully supported the implementation of autonomy. area . corruption in the regions, a factor in the potential emergence of conflicts between regions. To get out of the problems in the implementation of autonomy, it is necessary to have the concept of strengthening the authority of the governor in regional autonomy so that the acceleration of economic growth and development will require some reconstruction of authority, namely: reconstruction of authority based on legal certainty, reconstruction of authority based on justice, reconstruction of authority based on a unitary state, and reconstruction of authority based at the provincial government level.Keywords: Reconstruction, Strengthening authority